Adverse Drug Reactions: Knowledge, Attitude and Practice of Pharmacy - Maryam Etminani-Isfahani; Sarah Mousavi; Amin Rakhshan; Mehrdad Assarian; Leila Kuti; Kaveh Eslami (Research Center for Rational Use of Drugs (RCRUD), 2015)
Background: Adverse Drug Reactions (ADRs) are one of the leading causes of morbidity and mortality and contribute to excessive health care costs. Detection and reporting of ADRs could decrease these consequences. The present study was designed to assess the Knowledge, Attitude and Practice (KAP) of pharmacy students towards ADRs monitoring and reporting. Methods: A questionnaire was prepared to investigate the Knowledge, Attitude and Practice (KAP) of pharmacy students regarding ADR reporting. The questionnaire consisting of 17 questions (7 questions on knowledge, 5 on attitudes and 5 on practice) were given to pharmacy students randomly. Results: A total of 71 respondents participated in the study. 70% of participants had favorable general knowledge about ADRs but more than 60% of their professional knowledge was not satisfying. 60% of respondent believed that educational intervention will improve participating of health care professional in ADRs reporting. 63% of respondent observed ADRs cases but about 95% of them had never reported an ADR. Conclusion: In overall, pharmacy students have poor knowledge, attitude and practice towards ADRs reporting and pharmacovigilance. This suggests the need of suitable changes in the undergraduate teaching curriculum and additional training among the students regarding ADRs.